(untitled) (Enlace UIC: Revista de Investigación de la División de Posgrados de la Universidad Intercontinental, 2021)
As a result of culturally inherited stereotypes, men and their masculinity are viewed unfavourably. Currently, this has generated a deconstruction of the feminine and masculine in all areas.